2005
DOI: 10.1073/pnas.0505489102
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of the resistance of an insect carboxypeptidase to plant protease inhibitors

Abstract: Corn earworm (Helicoverpa zea), also called tomato fruitworm, is a common pest of many Solanaceous plants. This insect is known to adapt to the ingestion of plant serine protease inhibitors by using digestive proteases that are insensitive to inhibition. We have now identified a B-type carboxypeptidase of H. zea (CPBHz) insensitive to potato carboxypeptidase inhibitor (PCI) in corn earworm. To elucidate the structural features leading to the adaptation of the insect enzyme, the crystal structure of the recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 42 publications
(37 reference statements)
8
68
1
Order By: Relevance
“…Mammalian carboxypeptidase, an exopeptidase, has been well characterized (Titani et al, 1975;Rees et al, 1983;Coll et al, 1991;Guasch et al, 1992;Aloy et al, 1998), but the studies of insect carboxypeptidases are limited to a few species including black fly Simulium vittatum (Ramos et al, 1993), corn earworm Helicoverpa armingera (Bown et al, 1998;Bown and Gatehouse, 2004), mosquitoes Anopheles gambiae and Aedes aegypti (Edwards et al, 1997(Edwards et al, , 2000, tsetse fly Glossina morsitans (Yan et al, 2002), bertha armyworm Mamestra configurata (Hegedus et al, 2003), cabbage looper Trichoplusia ni (Wang et al, 2004), and corn earworm Helicoverpa zea (Bayes et al, 2005). In the current research, we report the isolation and characterization of nine unique cDNAs that encode carboxypeptidases from the Hessian fly, Mayetiola destructor (Say), one of the most destructive pests of wheat (Triticum aestivum L.) (Hatchett et al, 1987;Buntin, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian carboxypeptidase, an exopeptidase, has been well characterized (Titani et al, 1975;Rees et al, 1983;Coll et al, 1991;Guasch et al, 1992;Aloy et al, 1998), but the studies of insect carboxypeptidases are limited to a few species including black fly Simulium vittatum (Ramos et al, 1993), corn earworm Helicoverpa armingera (Bown et al, 1998;Bown and Gatehouse, 2004), mosquitoes Anopheles gambiae and Aedes aegypti (Edwards et al, 1997(Edwards et al, , 2000, tsetse fly Glossina morsitans (Yan et al, 2002), bertha armyworm Mamestra configurata (Hegedus et al, 2003), cabbage looper Trichoplusia ni (Wang et al, 2004), and corn earworm Helicoverpa zea (Bayes et al, 2005). In the current research, we report the isolation and characterization of nine unique cDNAs that encode carboxypeptidases from the Hessian fly, Mayetiola destructor (Say), one of the most destructive pests of wheat (Triticum aestivum L.) (Hatchett et al, 1987;Buntin, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There are examples of herbivore-inducible PIs with no defensive function or even the opposite effect due to the counteradaptations of insects to the ingestion of PIs (Zhu-Salzman et al, 2008). Several studies demonstrated that some insects respond with constitutive or induced production of PI-insensitive proteases (Jongsma et al, 1995;Bown et al, 1997;Bayé s et al, 2005Bayé s et al, , 2006 or by proteolytically inactivating the ingested PIs to prevent binding to sensitive proteases (Girard et al, 1998;Giri et al, 1998;Zhu-Salzman et al, 2003). For many insects, the ingestion of PI-containing tissues elicits behavioral and physiological counterresponses that increase the amount of damage they inflict on plants: sublethal PI levels stimulate feeding and induce a general overproduction of proteolytic enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…4). Herbivores can respond to high PI levels in the diet by (a) overproducing or down-regulating PI-sensitive proteinase (Broadway and DuVey 1986;Zavala et al 2008b), (b) overproducing PI-insensitive proteases (Bayes et al 2005;Jongsma et al 1995), (c) degrading the inhibitors (Giri et al 1998), or (d) changing their feeding positions on the plant . Selective feeding on older, more poorly defended soybean leaves may allow JBs to optimize their growth under a variety of atmospheric conditions.…”
Section: Discussionmentioning
confidence: 99%